Birth prevalence of exomphalos, associated anomalies and outcomes in England & Wales: 1997–2007. (16th November 2010) - Smith, CA; Bythell, M; Rounding, C; Draper, ES
Abstract : Background: The majority of cases of exomphalos are diagnosed during the antenatal period. Up-to-date information about associated anomalies and outcomes are required to facilitate counselling and management. Aim: To examine the trend in the birth prevalence of exomphalos in England & Wales (E&W) from 1997 to 2007. To describe associated anomalies, outcomes and survival to 1 year. Method: Data for all cases with exomphalos notified to eight Congenital Anomaly Registers across E&W, between 1997 and 2007, was analysed by year of birth. Results: 1191 cases of exomphalos were reported over the 11-year period. During this time the birth prevalence of exomphalos showed a significant increasing trend from 2.9 (95% CI 2.5 to 3.3) to 4.3 (3.9 to 4.7) per 10 000 births (X 2 test for trend, p<0.0001). 564 (47.4%) cases were electively terminated. 417 (35%) of all infants, were live born and 307 (25.8%) survived to 1 year of age. Of the 341 infants with isolated exomphalos, 197 (57.8%) were live born and 149 (43.7%) were reported to be alive at 1 year of age. Chromosomal anomalies were reported in 354 (29.7%) cases, two thirds of these cases were trisomy 18. The other most commonly reported associated anomalies were musculo-skeletal (31.9%), cardiac (20.7%) and neurological (13.4%). Conclusion: There was a significant increase in the birth prevalence of exomphalos in E&W from 1997 to 2007. Approximately half of all exomphalos cases were terminated and a further quarter survived to 1 year of age. However, survival in isolated exomphalos cases was significantly higher than in cases with associated anomalies (43.7% vs 18.6%).